Healthcare-associated urinary tract infection in the Surgery Department at Queen Elizabeth Central Hospital: Deciphering risk factors and antimicrobial resistance patterns of isolated bacteria - Gabriel, Kambale Bunduki (Kamuzu University of Health Sciences, 2022)
In this dissertation, I investigated the risk factors associated with healthcare-associated infections among patients admitted in surgical wards of the Surgery department of the Queen Elizabeth Central Hospital (QECH), Blantyre, Malawi. A particular focus was on healthcare-associated urinary tract infection (UTI). This dissertation is a result of three studies. The first one was a systematic review and meta-analysis of uropathogenic Escherichia coli (UPEC) and specifically their antimicrobial resistance and virulence profiles. The second study was a point-prevalence survey on healthcare-associated infections (HAI) and antimicrobial use in the surgery department at QECH. The third study was a cross-sectional study investigating risk factors associated with UTI and catheter-associated UTI. In addition, the study determined the antimicrobial resistance patterns of isolated bacteria from urine samples from patient suspected with hospital-acquired UTI. From the systematic review and meta-analysis, 1,888 UPEC isolates were included in the analysis. High antimicrobial resistance rates were observed among the antibiotic class of tetracycline in 69.1% (498/721), followed by sulphonamides in 59.3% (1119/1888), quinolones in 49.4% (1956/3956), and beta-lactams in 36.9% (4410/11964). Meanwhile, virulence factors with highest prevalence were immune suppressors (54.1%) followed by adhesins (45.9%). The point prevalence of HAI was 11.4% (n=12/105) (95% CI: 6.0%-19.1%), including 4 surgical site infections, 4 urinary tract infections, 3 bloodstream infections and 1 bone/joint infection. We identified the following risk factors for HAI; length-of-stay between 8 and 14 days (OR=14.4, 95% CI: 1.65-124.7, p=0.0143), presence of indwelling urinary catheter (OR=8.3, 95% CI: 2.24-30.70, p=0.003) and the history of surgery in the vii past 30 days (OR=5.11, 95% CI: 1.46-17.83, p=0.011). 29/105 patients (27.6%) were prescribed antimicrobials, most commonly the 3rd-generation cephalosporin, ceftriaxone (n=15). The prevalence of confirmed HA-UTI was 53.1% (179/337, 95% CI: 47.8-58.4). The CAUTI was observed in 53.9% (28/52, 95% CI: 40.0-67.1). Risk factors associated with HA-UTI and CAUTI were the age of patients, patients who are not married, low educational level (none or primary school), prostatic diseases, patients presenting UTI symptoms, hospital length of stay (>7 days). The most frequent isolated bacteria from patient with confirmed HA-UTI were E. coli in 46.4% (83/179), Klebsiella spp in 11.7% (21/179), Citrobacter spp in 9.5% (17/179), S. aureus in 5.9% (16/179), Enterobacter spp in 5.5% (10/179), Acinetobacter spp in 5% (9/179), Pseudomonas spp in 3.4% (6/179) and Enterococcus spp in 2.8% (5/179). Other emerging bacteria with potential of causing wide ranges of infections were also observed. These included Raoultella spp in 2.2% (4/179), Kluyvera ascorbata in 1.7% (3/179), Morganella morganii in 0.6% (1/179) and Proteus vulgaris in 0.6% (1/179). Resistance rates observed were 2.3% for carbapenems (meropenem and imipenem) (4/171 for each), 10.5% (18/171) for amikacin, 21.6% (36/167) for fosfomycin, 36.0% (58/161) for chloramphenicol, 50.1% (84/165) for nitrofurantoin, 53.9% (69/128) for amoxicillin-clavulanate and 54.0% (95/176) for ciprofloxacin. Healthcare-associated infections constitute a relatively high burden in the surgical ward of QECH. Reinforcing infection prevention and control measures will help in reducing their prevalence and hence reduce antimicrobial resistance. Empiric antibiotic therapy for UTI in the Surgery Department should be revised based on the antimicrobial resistance patterns of isolated bacteria.